Green Human Resource Management Practices in the Hotel Industry: Ethiopian Perspective - Chimedessa, Sintayehu Gurmessa; Chawla, Arvinder Singh (Gyan Management Journal, 2024)
This article’s primary focus is on the application of green HRM techniques by the hotel sector. Every subordinate and the management bodies must be committed to making the organization green. Nowadays, the larger picture of human resource management is examined in light of sustainability. The degree of application was examined by identifying and evaluating six key GHRM item components. Green employee empowerment and participation, green training and development, green performance management and appraisal, green reward and compensation, and green management of organizational culture were the highlighted GHRM practices. The degree and scope of green HR practices are evaluated using an exploratory research design. For this study, data from both primary and secondary sources were compiled. In order to update and validate the list of fundamental GHRM practices that had previously been found through literature reviews, input and suggestions from aspiring HR managers were now critically needed. According to the findings, the overall GHRM practice implementation is 2.07, which is regarded as a low level. Moreover, the statistical outcome indicates that workers are receiving compensation and benefits for their contributions even in the lack of appropriate eco-friendly hiring, training, and development guidelines. The results of statistical analysis indicated a strong positive correlation between environmental performance and the six green HRM practices.